2018
DOI: 10.1021/acs.energyfuels.7b03753
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Modified Seawater on Zeta Potential and Morphology of Calcite and Dolomite Aged with Stearic Acid

Abstract: Zeta potential measurements and microscopic surface characterization and imaging were conducted on calcite and dolomite crystals aged in stearic acid model oil and exposed to different synthetic brines representing different potential scenarios of injected seawater from the Arabian Gulf. Calcite particles were negatively charged in deionized water and maintained negative surface charges in all tested brines, except in diluted Arabian Gulf seawater that contained higher concentration of Ca2+ and Mg2+ ions. Dolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 68 publications
3
41
0
Order By: Relevance
“…Additionally, different types of outcrop chalk cores are shown to have different degree of reactivity towards SO 2− 4 ions [118]. Dolomite surfaces are suggested to behave similar to calcite surfaces in wettability alteration toward LSW [30,31,62,119]. However, it was suggested that, adsorption of stearic acid molecules on dolomite surfaces is stronger than on calcite surfaces, due to the positive surface charge of dolomite in diluted seawater [31].…”
Section: Rock Mineralogymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, different types of outcrop chalk cores are shown to have different degree of reactivity towards SO 2− 4 ions [118]. Dolomite surfaces are suggested to behave similar to calcite surfaces in wettability alteration toward LSW [30,31,62,119]. However, it was suggested that, adsorption of stearic acid molecules on dolomite surfaces is stronger than on calcite surfaces, due to the positive surface charge of dolomite in diluted seawater [31].…”
Section: Rock Mineralogymentioning
confidence: 99%
“…Dolomite surfaces are suggested to behave similar to calcite surfaces in wettability alteration toward LSW [30,31,62,119]. However, it was suggested that, adsorption of stearic acid molecules on dolomite surfaces is stronger than on calcite surfaces, due to the positive surface charge of dolomite in diluted seawater [31]. Consequently, diluted seawater is less efficient in altering the surface charge of dolomite and releasing adsorbed carboxylic acid materials when compared to calcite [31].…”
Section: Rock Mineralogymentioning
confidence: 99%
See 1 more Smart Citation
“…Stearic acid (Sa) has suitable phase transition temperature, higher phase transition enthalpy, and good thermal stability 16,17 . The modification of inorganic particles by Sa has also been reported 18–20 . Sa is made up of two parts: a hydrophobic tail and a hydrophilic head.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Yousef et al [28,29] confirmed that surface charge alteration of calcite toward more negative values, in the presence of diluted seawater, results in greater interactions with water molecules, and rock wettability alteration. Similarly, zeta potentials of calcite and dolomite surfaces conditioned with stearic acid are studied using synthetic diluted seawater [30]. It was shown that the calcite surfaces maintained negative zeta potential in the presence of deionised water, and in all the tested brines, excluding diluted seawater with higher concentration of cations (Ca 2+ and Mg 2+ ), which resulted in a positive zeta potential.…”
Section: Introductionmentioning
confidence: 99%